2006
DOI: 10.4049/jimmunol.176.2.984
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CD4+CD25+ and CD4+CD25− T Regulatory Cells on the Generation of Cytolytic T Cell Response to a Self but Human Tumor-Associated Epitope In Vitro

Abstract: CD4+ T cells naturally expressing CD25 molecules (natural T regulatory cells (Tregs)) have a role in maintaining self tolerance and in regulating responses to infectious agents, transplantation Ags, and tumor Ags. CD4+ Tregs induced from CD4+CD25− precursors (induced Tregs) also regulate immune responses in the periphery. However, which of these Tregs is a major impediment in generating antitumor CTL responses is not clear. We show that although the CD4+CD25+ subsets isolated from peripheral blood-derived lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(68 citation statements)
references
References 55 publications
(69 reference statements)
1
64
1
2
Order By: Relevance
“…4). Many previous studies have demonstrated the inhibition of tumor-specific CTL function by T regulatory cells [45,46]. In our studies, Survivin did not significantly alter Treg numbers or function (Supplementary Figure 5).…”
Section: Discussionsupporting
confidence: 59%
“…4). Many previous studies have demonstrated the inhibition of tumor-specific CTL function by T regulatory cells [45,46]. In our studies, Survivin did not significantly alter Treg numbers or function (Supplementary Figure 5).…”
Section: Discussionsupporting
confidence: 59%
“…135 Furthermore, although these studies have primarily focused on CD25 1 nTregs, it is likely that other Treg populations, such as Tr1 and Th3, also play a role in the suppression of immunity to tumours. 136,137 Depletion of Tregs may provide an effective means of improving the clinical effect of NY-ESO-1-based vaccines. Approaches include the use of low-dose cyclophosphamide 138 and ONTAK, a fusion toxin that targets cells via CD25.…”
Section: Approaches To Remove/inhibit Regulatory T Lymphocytes (Tregs)mentioning
confidence: 99%
“…For example, it has recently been shown that generation of antigen specific CD8 T cells failed in the presence of CD4 T cells. 52 This is the result of induction of T regulatory cells, which can significantly inhibit antigen specific MART-1 CTL induction. 52 It is interesting that significant 5T4 responses of CD4 T cell enriched populations are most apparent with depletion of the CD25 1 T cells (Elkord et al, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…52 This is the result of induction of T regulatory cells, which can significantly inhibit antigen specific MART-1 CTL induction. 52 It is interesting that significant 5T4 responses of CD4 T cell enriched populations are most apparent with depletion of the CD25 1 T cells (Elkord et al, unpublished data). This observation implies that the availability of the 5T4 repertoire of both CD4 and CD8 T cells may be optimally accessed in the absence of T regulatory activity.…”
Section: Discussionmentioning
confidence: 99%